Junior High School EFL Teachers’ Self-Efficacy in Multimodal Instruction - Efriansyah, Indo; Sukarno, Sukarno (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Advancements in digital technology have reshaped education, positioning multimodal instruction as a crucial pedagogical approach. This study aims to examine the level of teacher self-efficacy (TSE) in multimodal instruction among junior high school EFL teachers in Belitung Regency, Indonesia, and analyze variations based on age, gender, teaching experience, and certification status. Using a descriptive quantitative approach, data were collected from 47 teachers through an adapted Teacher Sense of Efficacy Scale (TSES). Results revealed a moderate level of TSE in multimodal instruction (M = 3.96, SD = 0.72), approaching the high category. Teachers expressed the highest confidence in classroom management (M = 4.01, SD = 0.72) and the lowest in instructional strategies (M = 3.93, SD = 0.74). Mid-career teachers (aged 31 – 50) and those with 5 – 15 years of experience reported the highest self-efficacy, while younger and older teachers showed lower confidence. Gender and certification status had minimal impact, suggesting that teaching experience and professional development are more influential. This study concludes that while teachers intuitively adopt multimodal strategies as a result of their immersion in the digital world and the technology-based training they receive, targeted support is needed to enhance their self-efficacy in multimodal instruction.